Pengaruh Komisaris Independen, Sales Growth, Profitabilitas, Firm Size dan Kepemilikan Institusional terhadap Tax Avoidance - Devi Putri Ayu Wulansari; Arief Himmawan Dwi Nugroho (Owner : Riset dan Jurnal Akuntansi, 2023)
Tax avoidance is an effort made to reduce the tax burden in order to obtain maximum profit in accordance with tax regulations. This study aims to identify whether independent commissioners, sales growth, profitability, firm size, and institutional ownership have an effect on tax avoidance. The object used in this study used the consumer cyclicals sector companies listed on the IDX for the period 2018 – 2021. The sampling technique used was a purposive sampling method with 68 companies over a 4 year period, resulting in a total sample of 272 research samples. The method in this study uses multiple linear regression analysis with quantitative data. Measurement of tax avoidance with the Effective Tax Rate (ETR) is obtained from income tax expense divided by profit before tax. Independent commissioners have no effect on tax avoidance. Sales growth has a negative and significant effect on tax avoidance. Profitability has a negative and significant effect on tax avoidance. Firm size has a negative and significant effect on tax avoidance. And institutional ownership has no effect on tax avoidance. The results of the F test were 16.391 and a significance value of 0.000 so that the regression model in the study was declared feasible or accepted. The adjusted R square test results of 0.325 (32.5%) variable tax avoidance are influenced by independent variables, namely independent commissioners, sales growth, profitability, firm size and institutional ownership.